Metasurface orbital angular momentum holography - Haoran Ren (Nature Portfolio, 2019)
Conventional hologram designs lack orbital angular momentum selectivity. Here, the authors design metasurface holograms consisting of GaN nanopillars with discrete spatial frequency distributions allowing the reconstruction of distinctive orbital angular momentumdependent holographic images.